2020
DOI: 10.2503/hortj.utd-175
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Begomoviruses Associated with Yellow Leaf Curl Disease in <i>Solanaceae</i> and <i>Cucurbitaceae</i> Crops from Northern Sumatra, Indonesia

Abstract: Begomoviruses, transmitted by whiteflies (Bemisia tabaci), have emerged as serious constraints to the cultivation of a wide variety of vegetable crops worldwide. Leaf samples from Solanaceae (tomato, tobacco, and eggplant) and Cucurbitaceae (cucumber and squash) plants exhibiting typical begomoviral yellowing and/or curling symptoms were collected in Northern Sumatra, Aceh province, Indonesia. Rolling circle amplification was conducted using DNA isolated from cucumber, squash, eggplant, and tobacco, and the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…4; Table 2). Previous diagnosis that detected begomovirus in Solanaceae crops (tomato, pepper, eggplant, and tobacco) in Aceh province, Indonesia, indicated that all diagnosed samples were negative for ToLCNDV infection and were only positive for other begomovirus species, such as pepper yellow leaf curl Indonesia virus, pepper yellow leaf curl Aceh virus, tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), and ageratum yellow vein virus (Kesumawati et al, 2019(Kesumawati et al, , 2020Koeda et al, 2016). It was reported that ToLCNDV-[OM] (DNA-A: GU180095) isolated from oriental melon (C. melo) in Taiwan infected cucurbit crops, but not tomato plants, by mechanical inoculation (Chang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4; Table 2). Previous diagnosis that detected begomovirus in Solanaceae crops (tomato, pepper, eggplant, and tobacco) in Aceh province, Indonesia, indicated that all diagnosed samples were negative for ToLCNDV infection and were only positive for other begomovirus species, such as pepper yellow leaf curl Indonesia virus, pepper yellow leaf curl Aceh virus, tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), and ageratum yellow vein virus (Kesumawati et al, 2019(Kesumawati et al, , 2020Koeda et al, 2016). It was reported that ToLCNDV-[OM] (DNA-A: GU180095) isolated from oriental melon (C. melo) in Taiwan infected cucurbit crops, but not tomato plants, by mechanical inoculation (Chang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…S1). DNA-A of ToLCNDV-[BACu-20] isolated from Indonesia in our previous study (Kesumawati et al, 2020) formed a clade with ToLCNDV isolates from Thailand, Indonesia, Laos, Taiwan, and Bangladesh (Fig. 3).…”
Section: Isolation Of Begomoviral Dnas From Cucurbit Crops and Sequence Analysismentioning
confidence: 93%
See 3 more Smart Citations